I-alowCD11bhigh DC Regulates the Immune Response in the Eyes of Experimental Autoimmune Uveitis. (10th March 2020) - Zhao, Yu; Wang, Jingwen; Min, Zhang; Peng, Li; Qi, Shuhong; Lin, Wei
Abstract : Regulatory dendritic cells (DCreg ) have been reported to be a negative regulator in the immune response. These cells are widely distributed in the liver, spleen, and lung. However, the status and function of DCreg in the eyes and disease are still not very clear. Herein, we found that the number of I-a low CD11b high DC increased in the eye and spleen at the recovery stage of experimental autoimmune uveitis (EAU), which is a mouse model for autoimmune uveitis. These cells expressed lower levels of CD80, CD86, and CD54 than the mature DCs and expressed interleukin 10 (IL-10), indoleamine 2, 3-dioxygenase (IDO), and transforming growth factor beta (TGF- β ) as well. Moreover, these DCreg can regulate the development of EAU by promoting CD4 + CD25 + Foxp3 + regulatory T cells. The increased interferon-gamma (IFN- γ ) in the aqueous humor of EAU participates in inducing DCreg to alleviate the symptom of EAU. Furthermore, DCreg was found to exist in the eyes of normal mice. Aqueous humor, containing a certain concentration of IL-10, TGF- β, prostaglandin E2 (PGE2), IDO, and nitric oxide (NO), induced the tolerance of DCreg in normal eyes. It can be concluded that DCreg exists in the eyes and plays a protective role in inflamed eyes. These DCreg induced by IFN- γ might be used as a strategy to develop therapy for EAU management.